Symmetry and perturbation theory : (World Scientific, 2002)
This is the fourth conference on "Supersymmetry and Perturbation Theory" (SPT 2002). The proceedings present original results and state-of-the-art reviews on topics related to symmetry, integrability and perturbation theory, etc.